Theory of puppets or theory of mind? Misunderstanding how children construe puppets in psychological research: A commentary on Packer and Moreno-Dulcey (2022) - Wellman, Henry M.; Yu, Chi-Lin (Cognitive development, 2022)
In a recent article in this journal, Packer and Moreno-Dulcey (2022) critique research on social cognition for so often using puppets and dolls in its research tasks instead of real persons. First, they suggest that such tasks have dubious validity including low ecological validity. Then they suggest when children’s performance on social-cognitive using puppets and dolls mirrors their performance with real people, children are pretending the puppets are real people. We argue that this misconstrues how children treat puppets in typical social-cognitive research: Children do not pretend puppets are people in such tasks; instead, they accept the experimental framing that the puppet represents a person. Children take the puppet as an acceptable and common stand-in for a person. •Critiques article and arguments by Packer & Moreno-Dulcey that sets the stage for this special issue.•Contends that Packer & Moreno-Dulcey misconstrue how children understand puppets used in social-cognition tasks.•Instead children treat puppets (and dolls) as straightforward person stand-ins, just as experimenters expect.